2021
DOI: 10.1021/acs.jpclett.1c00524
|View full text |Cite|
|
Sign up to set email alerts
|

Promoted Aggregation of Aβ on Lipid Bilayers in an Open Flowing System

Abstract: Self-assembly of amyloid-β (Aβ) peptides in nonequilibrium, flowing conditions is associated with pathogenesis of Alzheimer’s disease. We examined the role of biologically relevant, nonequilibrium, flowing conditions in the desorption, diffusion, and integration of Aβ-lipid assemblies at the membrane surface using a microchannel connected with microsyringes. A 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) bilayer was formed on a glass substrate and incubated in Aβ solution under either a quiescent conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A recent study of Aβ fibril formation in flow conditions concluded that early forming fibrils and membranes form an equilibrium between the membrane-bound peptide and peptide–lipid aggregates in solution. This process implicitly favors the incorporation of lipids into fibrils at an early stage of fibril formation ( 143 ). This stage of the process is where the most toxic membrane-active species form and corresponds to the formation of compact structures in AD ( Fig.…”
Section: When and How Are Lipids Incorporated Into Fibrils?mentioning
confidence: 99%
“…A recent study of Aβ fibril formation in flow conditions concluded that early forming fibrils and membranes form an equilibrium between the membrane-bound peptide and peptide–lipid aggregates in solution. This process implicitly favors the incorporation of lipids into fibrils at an early stage of fibril formation ( 143 ). This stage of the process is where the most toxic membrane-active species form and corresponds to the formation of compact structures in AD ( Fig.…”
Section: When and How Are Lipids Incorporated Into Fibrils?mentioning
confidence: 99%
“…While shear-induced monomeric protein dynamics were explored by experimental , and computational studies, and lipid systems were also investigated under shear flows, we still lack an atomic description of Aβ aggregates under fluid flows in the bulk solution and at the surface of membranes. Yet is it known that flowing acting on the membrane surface showed desorption, diffusion and collision of Aβ-lipid aggregates forming larger plaque-like aggregates . Overall, hydrodynamic flow fields in ISS are likely to change the conformational ensemble states assessed by small Aβ oligomers and may promote very rare excited oligomers …”
Section: Resultsmentioning
confidence: 99%
“…More elaborated microfluidic experiments could also approach in vivo conditions. 120,125,142 These combined studies could help design more efficient drugs targeting Aβ monomer and oligomers. 135,143…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations